2017
DOI: 10.1016/j.wsj.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and inter-comparison of infiltration models

Abstract: Infiltration models are very helpful in designing and evaluating surface irrigation systems. The main objective of the present work is estimation and inter-comparison of infiltration models which are used to evaluate the infiltration rates of National Institute of Technology (NIT)-campus in district of Kurukshetra, Haryana (India) and for this study, field infiltration tests were carried out at ten different locations comprising of 109 observations by use of double ring infiltrometer. The potential of three in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 10 publications
0
45
0
3
Order By: Relevance
“…The Novel model represents the infiltration rate of soil with the highest accuracy, followed by the RF model. The Novel model proposed by Sihag et al (2017) was observed to work reasonably well in comparison to other aforesaid empirical models, while the RF model is better relative to ANFIS-based soft computing models. As can be inferred from Figure 11, the points simulated by the Novel and RF models precisely follow the path of the actual infiltration rate and ensure their suitability in approximating the infiltration rate of soil in the field.…”
Section: Comparative Analysis Of Machine-learning-based Models and Emmentioning
confidence: 87%
See 3 more Smart Citations
“…The Novel model represents the infiltration rate of soil with the highest accuracy, followed by the RF model. The Novel model proposed by Sihag et al (2017) was observed to work reasonably well in comparison to other aforesaid empirical models, while the RF model is better relative to ANFIS-based soft computing models. As can be inferred from Figure 11, the points simulated by the Novel and RF models precisely follow the path of the actual infiltration rate and ensure their suitability in approximating the infiltration rate of soil in the field.…”
Section: Comparative Analysis Of Machine-learning-based Models and Emmentioning
confidence: 87%
“…As can be inferred from Figure 11, the points simulated by the Novel and RF models precisely follow the path of the actual infiltration rate and ensure their suitability in approximating the infiltration rate of soil in the field. The Novel model proposed by Sihag et al (2017) was observed to work reasonably well in comparison to other aforesaid empirical models, while the RF model is better relative to ANFIS-based soft computing models. Despite the better performance of the Novel model, knowledge of equation parameters respective to the location is necessary for their application, very similar to other empirical models (KM and MKM).…”
Section: Comparative Analysis Of Machine-learning-based Models and Emmentioning
confidence: 87%
See 2 more Smart Citations
“…Segundo Sihag et al (2017), os erros podem ser minimizados a partir do incremento temporal do experimento, uma vez que os modelos KO, KL e SCS têm melhor desempenho para simulações com tempos mais longos.…”
Section: Eficiência Da Modelagemunclassified